Anthraquinone hydrogenation catalyst and method for preparing the same

CN121042022BActive Publication Date: 2026-10-27YANTAI TENGSHENG NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511267267.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-05
Publication Date
2026-10-27
Estimated Expiration
2045-09-05

AI Technical Summary

Technical Problem

采用该制备方法制备得到的负载型Pd基颗粒催化剂可用于烷基蒽醌加氢反应,虽然一定程度上提高了催化活性,但制备工艺较为复杂

Benefits of technology

[0020]与现有技术相比,本发明的有益效果:通过多次浸渍、焙烧工艺制备了蒽醌加氢催化剂。在铈元素的基础上,通过引入适量的锆、锌复合过渡金属氧化物,增加催化剂的比表面积,提高金属钯分散度,增强了催化剂的稳定性,改善了活性组分与载体之间的相互作用,有效提高了催化剂的蒽醌加氢活性。催化剂制备简单,反应条件温和,符合工业生产的要求,能够达到工业化应用的目的。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application belongs to the technical field of catalyst preparation, and particularly relates to an anthraquinone hydrogenation catalyst and a preparation method thereof. The preparation method of the anthraquinone hydrogenation catalyst comprises the following steps: (1) impregnating an alumina carrier with a mixed solution of zirconium salt and zinc salt, and then drying and calcining to obtain a modified alumina carrier; (2) impregnating the modified alumina carrier with a mixed solution of cerium salt and palladium salt, and then drying, calcining and hydrogen reduction to obtain the anthraquinone hydrogenation catalyst. On the basis of cerium elements, by introducing appropriate amounts of zirconium and zinc composite transition metal oxides, the specific surface area of the catalyst is increased, the dispersion degree of the metal palladium is improved, the stability of the catalyst is enhanced, the interaction between the active component and the carrier is improved, and the anthraquinone hydrogenation activity of the catalyst is effectively improved. The catalyst is simple to prepare, the reaction conditions are mild, meets the requirements of industrial production, and can achieve the purpose of industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst preparation technology, specifically relating to an anthraquinone hydrogenation catalyst and its preparation method. Background Technology

[0002] Hydrogen peroxide is an important inorganic fine chemical with strong oxidizing properties and environmentally friendly use. It is widely used in chemical synthesis, textiles (bleaching of wool and cotton fabrics), pharmaceuticals (sterilization and disinfection), papermaking (bleaching wood pulp), food (sterilization and disinfection of food and its packaging), cosmetics, metallurgy, military industry, and wastewater treatment.

[0003] The main methods for synthesizing hydrogen peroxide are the anthraquinone process, the oxygen cathode reduction process, and the direct hydrogen-oxygen synthesis process. Among these, the anthraquinone process has advantages such as low raw material cost and low energy consumption, making it the most commonly used method for industrial hydrogen peroxide production. Currently, nearly 98% of the world's hydrogen peroxide is produced using the anthraquinone process. The anthraquinone process includes four steps: hydrogenation, oxidation, extraction, and post-treatment. This process is mainly based on anthraquinone and its derivatives (usually 2-ethylanthraquinone). Under the action of a catalyst, it first reacts with hydrogen to produce 2-alkylanthraquinone. The working solution containing anthraquinone is then transferred to an oxidation reactor, where air is introduced to oxidize the reaction solution, reducing it back to 2-alkylanthraquinone and hydrogen peroxide. Based on the principle of "like dissolves like," hydrogen peroxide is more soluble in water. Utilizing the density difference between the working solution and water, hydrogen peroxide can be obtained by repeated extraction with deionized water. The working solution can be reprocessed to achieve the recycling of raw materials, improving the economic value of the anthraquinone process for producing hydrogen peroxide.

[0004] In actual production processes, to promote the efficient conversion of anthraquinone molecules to active anthraquinone, industrial processes typically use hydrogen in quantities far exceeding the stoichiometric ratio to enhance the reaction's effectiveness. However, the introduction of large amounts of hydrogen leads to significant resource waste, increases safety hazards in industrial production, and causes excessive hydrogen molecules to be activated and stored at active sites, thereby inhibiting the adsorption of the reactant anthraquinone molecules. Therefore, although the anthraquinone process for producing hydrogen peroxide is a relatively mature industrial technology, research on this reaction has never ceased. Developing more efficient anthraquinone hydrogenation catalysts is of paramount importance for the efficient production of hydrogen peroxide and for sustainable green development.

[0005] Chinese invention patent application CN117816153A discloses a method for preparing a supported Pd-based catalyst and its application, comprising the following steps: (1) mixing a support with a Pd precursor solution, impregnating the solution, filtering, washing, drying, and pre-reducing to obtain a catalyst precursor; (2) microwaving the catalyst precursor, followed by reduction treatment to obtain a supported Pd-based catalyst. The supported Pd-based particulate catalyst prepared by this method can be used for the hydrogenation reaction of alkyl anthraquinones. Although it improves catalytic activity to some extent, the preparation process is relatively complex. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides an anthraquinone hydrogenation catalyst and its preparation method. By adding various metal element promoters to increase the exposure rate of active metals, the hydrogenation efficiency is successfully improved while reducing the amount of palladium used in the anthraquinone hydrogenation catalyst.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing an anthraquinone hydrogenation catalyst includes the following steps: (1) A modified alumina carrier was obtained by impregnating the alumina carrier with a mixed solution of zirconium salt and zinc salt, followed by drying and calcination. (2) The modified alumina support is impregnated with a mixed solution of cerium salt and palladium salt, and then dried, calcined and reduced with hydrogen to obtain an anthraquinone hydrogenation catalyst. In the anthraquinone hydrogenation catalyst, based on the mass of the alumina support, the Zr content is 2-5wt%, the Zn content is 1-3wt%, and the Ce content is greater than 0 and less than or equal to 0.5wt%.

[0008] Traditional supported catalysts are often prepared using aqueous solution impregnation. However, due to the solvation effect of the impregnation solvent and the clustering effect of the active components, the active components are difficult to disperse. Furthermore, during subsequent reduction and heat treatment, the microcrystals of the active components easily agglomerate and aggregate, ultimately resulting in poor dispersibility and severely affecting the catalytic performance. Existing technologies generally use rare earth elements to improve catalyst activity. Among them, cerium can alter the electronic structure of the active components, optimizing their geometry. The introduction of cerium has the greatest effect on improving palladium dispersion, which is beneficial for the full exposure of active sites. However, the modifying effect of cerium alone is limited, and it can easily lead to a decrease in the activity of the active components or even their detachment during use.

[0009] Building upon this foundation, the present invention incorporates zirconium and zinc salt composite metal elements. By introducing appropriate amounts of zirconium and zinc composite transition metal oxides, the specific surface area of ​​the catalyst can be increased, the palladium concentration on the catalyst surface can be increased, and the dispersion of palladium metal can be further improved, thereby enhancing the hydrogenation activity of the catalyst. As transition metal elements, zirconium and zinc are widely available and readily available raw materials. Moreover, zirconium and zinc belong to different groups of elements; when used in combination, the difference in their electron shell numbers is more conducive to improving the stability of the alumina support, enhancing the interaction between the active component palladium and the alumina support, and promoting the dispersion performance of the active component palladium. The amount of zirconium and zinc salts used is not particularly limited. Zirconium oxides with higher atomic numbers are more effective in suppressing the high-temperature phase transition of alumina and improving the stability of the catalyst.

[0010] In particular, zirconium salts are used in greater quantities than zinc salts, and the differentiated configuration of different transition metal elements can better improve the dispersion of the active components. Furthermore, based on the mass of the alumina support, the Zr content is 2-4 wt%, the Zn content is 1-2 wt%, the Ce content is 0.08-0.15 wt%, and the Pd content is 0.1-1 wt%. Notably, the cerium content is lower than that of palladium. An appropriate amount of cerium can both promote the dispersion of the palladium active component and prevent the formation of excessively large grains.

[0011] In one embodiment, the zirconium salt in step (1) is any one of zirconium nitrate, zirconium chloride, and zirconium sulfate; the zinc salt is any one of zinc chloride, zinc nitrate, zinc sulfate, and zinc acetate.

[0012] In one embodiment, the alumina support in step (1) is γ-alumina with a specific surface area of ​​150-250 m². 2 / g, with a pore size of 6-12nm. In particular, the alumina support is calcined γ-alumina.

[0013] In one embodiment, the drying temperature in step (1) is 100-130℃; the calcination temperature is 540-620℃; and the calcination time is 2-4 hours. Appropriate calcination temperature and time can both promote crystal formation and prevent the collapse of the porous structure caused by over-calcination.

[0014] In one embodiment, the anthraquinone hydrogenation catalyst contains 0.1-1 wt% Pd, based on the mass of the alumina support. For ease of calculation, this invention uses the mass of the alumina support as a basis and determines the content of each metal element based on the mass ratio of the palladium element's own weight to the mass of the alumina support.

[0015] In one embodiment, the cerium salt in step (2) is either cerium nitrate or cerium chloride; and the palladium salt is either palladium chloride or palladium acetate.

[0016] In one embodiment, the drying temperature in step (2) is 110-130℃; the calcination temperature is 550-600℃; and the calcination time is 2-4h.

[0017] In one embodiment, the hydrogen reduction temperature in step (2) is 250-350°C.

[0018] In one embodiment, the impregnation in steps (1) and (2) is equal-volume impregnation. In this invention, both the active component and the co-active component are loaded onto the alumina support using an equal-volume impregnation process. Equal-volume impregnation means that the volume of the alumina support and the volume of the impregnation liquid are the same, allowing the impregnation liquid to completely enter the pores of the alumina support. This allows for convenient control of the loading amount of the active and co-active components, and the loading amount is easily calculated. Specifically, based on the volumes of the alumina support and the modified alumina support, solutions with corresponding contents (calculated as metal elements) of the active and co-active components are prepared, wherein the ratio of the mass of the metal element in the solution to the mass of the alumina support is the content of the corresponding component. In particular, multiple equal-volume impregnations can be used to improve the dispersibility of the components.

[0019] On the other hand, the present invention also provides an anthraquinone hydrogenation catalyst obtained by the above preparation method. By adding various metal element promoters to increase the exposure rate of active palladium, the hydrogenation efficiency is successfully improved while reducing the amount of palladium used in the anthraquinone hydrogenation catalyst. Specifically, a working solution is prepared, a certain amount of catalyst is added to carry out the reaction, and then the hydrogenation efficiency of the catalyst is tested by oxygen oxidation and potassium permanganate solution titration analysis.

[0020] Compared with existing technologies, the present invention offers the following advantages: An anthraquinone hydrogenation catalyst was prepared through a multiple impregnation and calcination process. Based on cerium, the introduction of appropriate amounts of zirconium-zinc composite transition metal oxides increases the catalyst's specific surface area, improves palladium dispersion, enhances catalyst stability, and improves the interaction between the active component and the support, effectively increasing the catalyst's anthraquinone hydrogenation activity. The catalyst preparation is simple, the reaction conditions are mild, meeting the requirements of industrial production and enabling industrial application. Detailed Implementation

[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] The methods for evaluating catalyst activity in Examples 1-10 and Comparative Examples 1-3 are as follows: The reactant was 2-ethylanthraquinone (EAQ), prepared as a 130 g / L anthraquinone solution using a mixture of trioctyl phosphate and C9 heavy aromatics (volume ratio 25:75) as the solvent. 60 mL of the anthraquinone solution and 1.1 g of palladium catalyst for anthraquinone hydrogenation were added to the reactor, using hydrogen as the feedstock. The reaction pressure was maintained at 0.3 MPa, and the catalytic hydrogenation performance of the catalyst was evaluated under the following conditions: stirring rate 800 rpm, temperature 60 °C, and time 70 min.

[0023] Example 1 A method for preparing an anthraquinone hydrogenation catalyst includes the following steps: (1) Based on the water absorption rate of the alumina support, a mixed solution containing zirconium nitrate and zinc nitrate was prepared, and the alumina support was impregnated with an equal volume of this mixed solution. After drying and calcination, a modified alumina support was obtained. The alumina support was γ-alumina with a specific surface area of ​​193.5 m². 2 / g, pore size 8.86nm; drying temperature 105℃; calcination temperature 540℃, calcination time 4h; (2) Based on the water absorption rate of the modified alumina support, a mixed solution containing cerium nitrate and palladium chloride was prepared, and the modified alumina support was impregnated with the mixed solution in equal volume. Then, after drying, calcination, and hydrogen reduction, an anthraquinone hydrogenation catalyst was obtained. In this anthraquinone hydrogenation catalyst, based on the mass of the alumina support, the Zr content was 2 wt%, the Zn content was 1 wt%, the Ce content was 0.08 wt%, and the Pd content was 0.3 wt%; the drying temperature was 110℃; the calcination temperature was 550℃, the calcination time was 4 h; and the hydrogen reduction temperature was 270℃. The hydrogenation efficiency of this anthraquinone hydrogenation catalyst was measured to be 10.9 g / L.

[0024] Example 2 A method for preparing an anthraquinone hydrogenation catalyst includes the following steps: (1) Based on the water absorption rate of the alumina support, a mixed solution containing zirconium nitrate and zinc nitrate was prepared, and the alumina support was impregnated with an equal volume of this mixed solution. After drying and calcination, a modified alumina support was obtained. The alumina support was γ-alumina with a specific surface area of ​​193.5 m². 2 / g, pore size 8.86nm; drying temperature 130℃; calcination temperature 620℃, calcination time 2h; (2) Based on the water absorption rate of the modified alumina support, a mixed solution containing cerium nitrate and palladium chloride was prepared, and the modified alumina support was impregnated with the mixed solution in equal volume. Then, after drying, calcination, and hydrogen reduction, an anthraquinone hydrogenation catalyst was obtained. In this anthraquinone hydrogenation catalyst, based on the mass of the alumina support, the Zr content was 5wt%, the Zn content was 3wt%, the Ce content was 0.2wt%, and the Pd content was 0.3wt%; the drying temperature was 130℃; the calcination temperature was 600℃, the calcination time was 2h; and the hydrogen reduction temperature was 300℃. The hydrogenation efficiency of this anthraquinone hydrogenation catalyst was measured to be 11.6 g / L.

[0025] Example 3 A method for preparing an anthraquinone hydrogenation catalyst includes the following steps: (1) Based on the water absorption rate of the alumina support, a mixed solution containing zirconium nitrate and zinc nitrate was prepared, and the alumina support was impregnated with an equal volume of this mixed solution. After drying and calcination, a modified alumina support was obtained. The alumina support was γ-alumina with a specific surface area of ​​193.5 m². 2 / g, pore size 8.86nm; drying temperature 115℃; calcination temperature 590℃, calcination time 3.2h; (2) Based on the water absorption rate of the modified alumina support, a mixed solution containing cerium nitrate and palladium chloride was prepared, and the modified alumina support was impregnated with the mixed solution in equal volume. Then, after drying, calcination, and hydrogen reduction, an anthraquinone hydrogenation catalyst was obtained. In this anthraquinone hydrogenation catalyst, based on the mass of the alumina support, the Zr content was 2wt%, the Zn content was 3wt%, the Ce content was 0.15wt%, and the Pd content was 0.3wt%; the drying temperature was 120℃; the calcination temperature was 570℃, the calcination time was 3.2h; and the hydrogen reduction temperature was 280℃. The hydrogenation efficiency of this anthraquinone hydrogenation catalyst was measured to be 10.8 g / L.

[0026] Example 4 A method for preparing an anthraquinone hydrogenation catalyst includes the following steps: (1) Based on the water absorption rate of the alumina support, a mixed solution containing zirconium nitrate and zinc nitrate was prepared, and the alumina support was impregnated with an equal volume of this mixed solution. After drying and calcination, a modified alumina support was obtained. The alumina support was γ-alumina with a specific surface area of ​​193.5 m². 2 / g, pore size 8.86nm; drying temperature 110℃; calcination temperature 550℃, calcination time 3.5h; (2) Based on the water absorption rate of the modified alumina support, a mixed solution containing cerium nitrate and palladium chloride was prepared, and the modified alumina support was impregnated with the mixed solution in equal volume. Then, after drying, calcination, and hydrogen reduction, an anthraquinone hydrogenation catalyst was obtained. In this anthraquinone hydrogenation catalyst, based on the mass of the alumina support, the Zr content was 2.5 wt%, the Zn content was 1.6 wt%, the Ce content was 0.11 wt%, and the Pd content was 0.3 wt%; the drying temperature was 115℃; the calcination temperature was 560℃, the calcination time was 3.6 h; and the hydrogen reduction temperature was 275℃. The hydrogenation efficiency of this anthraquinone hydrogenation catalyst was measured to be 12.1 g / L.

[0027] Example 5 A method for preparing an anthraquinone hydrogenation catalyst includes the following steps: (1) Based on the water absorption rate of the alumina support, a mixed solution containing zirconium nitrate and zinc nitrate was prepared, and the alumina support was impregnated with an equal volume of this mixed solution. After drying and calcination, a modified alumina support was obtained. The alumina support was γ-alumina with a specific surface area of ​​193.5 m². 2 / g, pore size 8.86nm; drying temperature 115℃; calcination temperature 590℃, calcination time 3.2h; (2) Based on the water absorption rate of the modified alumina support, a mixed solution containing cerium nitrate and palladium chloride was prepared, and the modified alumina support was impregnated with the mixed solution in equal volume. Then, after drying, calcination, and hydrogen reduction, an anthraquinone hydrogenation catalyst was obtained. In this anthraquinone hydrogenation catalyst, based on the mass of the alumina support, the Zr content was 3wt%, the Zn content was 2wt%, the Ce content was 0.05wt%, and the Pd content was 0.3wt%; the drying temperature was 120℃; the calcination temperature was 570℃, the calcination time was 3.2h; and the hydrogen reduction temperature was 280℃. The hydrogenation efficiency of this anthraquinone hydrogenation catalyst was measured to be 10.6 g / L.

[0028] Example 6 A method for preparing an anthraquinone hydrogenation catalyst includes the following steps: (1) Based on the water absorption rate of the alumina support, a mixed solution containing zirconium nitrate and zinc nitrate was prepared, and the alumina support was impregnated with an equal volume of this mixed solution. After drying and calcination, a modified alumina support was obtained. The alumina support was γ-alumina with a specific surface area of ​​193.5 m². 2 / g, pore size 8.86nm; drying temperature 125℃; calcination temperature 610℃, calcination time 2.5h; (2) Based on the water absorption rate of the modified alumina support, a mixed solution containing cerium nitrate and palladium chloride was prepared, and the modified alumina support was impregnated with the mixed solution in equal volume. Then, after drying, calcination, and hydrogen reduction, an anthraquinone hydrogenation catalyst was obtained. In this anthraquinone hydrogenation catalyst, based on the mass of the alumina support, the Zr content was 4.4 wt%, the Zn content was 2.6 wt%, the Ce content was 0.18 wt%, and the Pd content was 0.3 wt%. The drying temperature was 126 °C; the calcination temperature was 590 °C, and the calcination time was 2.6 h; the hydrogen reduction temperature was 290 °C. The hydrogenation efficiency of this anthraquinone hydrogenation catalyst was measured to be 12.3 g / L.

[0029] Example 7 A method for preparing an anthraquinone hydrogenation catalyst includes the following steps: (1) Based on the water absorption rate of the alumina support, a mixed solution containing zirconium nitrate and zinc nitrate was prepared, and the alumina support was impregnated with an equal volume of this mixed solution. After drying and calcination, a modified alumina support was obtained. The alumina support was γ-alumina with a specific surface area of ​​193.5 m². 2 / g, pore size 8.86nm; drying temperature 115℃; calcination temperature 590℃, calcination time 3.2h; (2) Based on the water absorption rate of the modified alumina support, a mixed solution containing cerium nitrate and palladium chloride was prepared, and the modified alumina support was impregnated with the mixed solution in equal volume. Then, after drying, calcination, and hydrogen reduction, an anthraquinone hydrogenation catalyst was obtained. In this anthraquinone hydrogenation catalyst, based on the mass of the alumina support, the Zr content was 3wt%, the Zn content was 2wt%, the Ce content was 0.5wt%, and the Pd content was 0.3wt%; the drying temperature was 120℃; the calcination temperature was 570℃, the calcination time was 3.2h; and the hydrogen reduction temperature was 280℃. The hydrogenation efficiency of this anthraquinone hydrogenation catalyst was measured to be 11.5 g / L.

[0030] Example 8 A method for preparing an anthraquinone hydrogenation catalyst includes the following steps: (1) Based on the water absorption rate of the alumina support, a mixed solution containing zirconium nitrate and zinc nitrate was prepared, and the alumina support was impregnated with an equal volume of this mixed solution. After drying and calcination, a modified alumina support was obtained. The alumina support was γ-alumina with a specific surface area of ​​193.5 m². 2 / g, pore size 8.86nm; drying temperature 109℃; calcination temperature 605℃, calcination time 2.7h; (2) Based on the water absorption rate of the modified alumina support, a mixed solution containing cerium nitrate and palladium chloride was prepared, and the modified alumina support was impregnated with the mixed solution in equal volume. Then, after drying, calcination, and hydrogen reduction, an anthraquinone hydrogenation catalyst was obtained. In the anthraquinone hydrogenation catalyst, based on the mass of the alumina support, the Zr content was 4 wt%, the Zn content was 2.2 wt%, the Ce content was 0.1 wt%, and the Pd content was 0.3 wt%. The drying temperature was 118℃; the calcination temperature was 574℃, and the calcination time was 3.4 h; the hydrogen reduction temperature was 285℃. The hydrogenation efficiency of this anthraquinone hydrogenation catalyst was measured to be 12.8 g / L.

[0031] Example 9 A method for preparing an anthraquinone hydrogenation catalyst includes the following steps: (1) Based on the water absorption rate of the alumina support, a mixed solution containing zirconium nitrate and zinc nitrate was prepared, and the alumina support was impregnated with an equal volume of this mixed solution. After drying and calcination, a modified alumina support was obtained. The alumina support was γ-alumina with a specific surface area of ​​193.5 m². 2 / g, pore size 8.86nm; drying temperature 122℃; calcination temperature 596℃, calcination time 3h; (2) Based on the water absorption rate of the modified alumina support, a mixed solution containing cerium nitrate and palladium chloride was prepared, and the modified alumina support was impregnated with the mixed solution in equal volume. Then, after drying, calcination, and hydrogen reduction, an anthraquinone hydrogenation catalyst was obtained. In this anthraquinone hydrogenation catalyst, based on the mass of the alumina support, the Zr content was 3.6 wt%, the Zn content was 1.9 wt%, the Ce content was 0.13 wt%, and the Pd content was 0.3 wt%. The drying temperature was 123℃; the calcination temperature was 582℃, and the calcination time was 3.3 h; the hydrogen reduction temperature was 285℃. The hydrogenation efficiency of this anthraquinone hydrogenation catalyst was measured to be 11.7 g / L.

[0032] Example 10 A method for preparing an anthraquinone hydrogenation catalyst includes the following steps: (1) Based on the water absorption rate of the alumina support, a mixed solution containing zirconium nitrate and zinc nitrate was prepared, and the alumina support was impregnated with an equal volume of this mixed solution. After drying and calcination, a modified alumina support was obtained. The alumina support was γ-alumina with a specific surface area of ​​193.5 m². 2 / g, pore size 8.86nm; drying temperature 115℃; calcination temperature 590℃, calcination time 3.2h; (2) Based on the water absorption rate of the modified alumina support, a mixed solution containing cerium nitrate and palladium chloride was prepared, and the modified alumina support was impregnated with the mixed solution in equal volume. Then, after drying, calcination, and hydrogen reduction, an anthraquinone hydrogenation catalyst was obtained. In this anthraquinone hydrogenation catalyst, based on the mass of the alumina support, the Zr content was 3wt%, the Zn content was 2wt%, the Ce content was 0.15wt%, and the Pd content was 0.3wt%; the drying temperature was 120℃; the calcination temperature was 570℃, the calcination time was 3.2h; and the hydrogen reduction temperature was 280℃. The hydrogenation efficiency of this anthraquinone hydrogenation catalyst was measured to be 12.9 g / L.

[0033] Comparative Example 1 A method for preparing an anthraquinone hydrogenation catalyst includes the following steps: (1) Based on the water absorption rate of the alumina support, a solution containing zirconium nitrate was prepared, and the alumina support was impregnated with an equal volume of this solution. After drying and calcination, a modified alumina support was obtained. The alumina support was γ-alumina with a specific surface area of ​​193.5 m². 2 / g, pore size 8.86nm; drying temperature 115℃; calcination temperature 590℃, calcination time 3.2h; (2) Based on the water absorption rate of the modified alumina support, a mixed solution containing cerium nitrate and palladium chloride was prepared, and the modified alumina support was impregnated with the mixed solution in equal volume. Then, after drying, calcination, and hydrogen reduction, an anthraquinone hydrogenation catalyst was obtained. In this anthraquinone hydrogenation catalyst, based on the mass of the alumina support, the Zr content was 5 wt%, the Ce content was 0.15 wt%, and the Pd content was 0.3 wt%; the drying temperature was 120℃; the calcination temperature was 570℃, the calcination time was 3.2 h; and the hydrogen reduction temperature was 280℃. The hydrogenation efficiency of this anthraquinone hydrogenation catalyst was measured to be 7.5 g / L.

[0034] Comparative Example 2 A method for preparing an anthraquinone hydrogenation catalyst includes the following steps: (1) Based on the water absorption rate of the alumina support, a solution containing zinc nitrate was prepared, and the alumina support was impregnated with an equal volume of this solution. After drying and calcination, a modified alumina support was obtained. The alumina support was γ-alumina with a specific surface area of ​​193.5 m². 2 / g, pore size 8.86nm; drying temperature 115℃; calcination temperature 590℃, calcination time 3.2h; (2) Based on the water absorption rate of the modified alumina support, a mixed solution containing cerium nitrate and palladium chloride was prepared, and the modified alumina support was impregnated with the mixed solution in equal volume. Then, after drying, calcination, and hydrogen reduction, an anthraquinone hydrogenation catalyst was obtained. In this anthraquinone hydrogenation catalyst, based on the mass of the alumina support, the Zn content was 5 wt%, the Ce content was 0.15 wt%, and the Pd content was 0.3 wt%; the drying temperature was 120℃; the calcination temperature was 570℃, the calcination time was 3.2 h; and the hydrogen reduction temperature was 280℃. The hydrogenation efficiency of this anthraquinone hydrogenation catalyst was measured to be 7.2 g / L.

[0035] Comparative Example 3 A method for preparing an anthraquinone hydrogenation catalyst includes the following steps: (1) Based on the water absorption rate of the alumina support, a mixed solution containing zirconium nitrate, zinc nitrate, and cerium nitrate was prepared, and the alumina support was impregnated with an equal volume of this mixed solution. After drying and calcination, a modified alumina support was obtained. The alumina support was γ-alumina with a specific surface area of ​​193.5 m². 2 / g, pore size 8.86nm; drying temperature 115℃; calcination temperature 590℃, calcination time 3.2h; (2) Based on the water absorption rate of the modified alumina support, a solution containing palladium chloride was prepared, and the modified alumina support was impregnated with the solution in equal volume. Then, after drying, calcination, and hydrogen reduction, an anthraquinone hydrogenation catalyst was obtained. In this anthraquinone hydrogenation catalyst, based on the mass of the alumina support, the Zr content was 3wt%, the Zn content was 2wt%, the Ce content was 0.15wt%, and the Pd content was 0.3wt%; the drying temperature was 120℃; the calcination temperature was 570℃, the calcination time was 3.2h; and the hydrogen reduction temperature was 280℃. The hydrogenation efficiency of this anthraquinone hydrogenation catalyst was measured to be 8.1 g / L.

[0036] As can be seen from the above examples and comparative examples, this invention adds zirconium and zinc salt composite metal elements to the traditional cerium salt modification. By introducing an appropriate amount of zirconium and zinc composite transition metal oxides, the specific surface area of ​​the catalyst can be increased, the palladium concentration on the catalyst surface can be increased, and the dispersion of palladium metal can be further improved, thereby enhancing the hydrogenation activity of the catalyst. As transition metal elements, zirconium and zinc are widely available and the raw materials are readily available; moreover, zirconium and zinc belong to different groups of elements, and the difference in the number of electron shells makes it more beneficial to improve the stability of the alumina support when used in combination, improve the interaction between the active component palladium and the alumina support, and promote the dispersion performance of the active component.

[0037] Compared to Example 10, Comparative Examples 1 and 2 lacked zirconium or zinc transition metal elements, respectively, resulting in reduced hydrogenation efficiency. This indicates that the differentiated configuration of zirconium and zinc elements with different electron shell numbers can better improve the dispersion of active components and enhance catalytic activity. In Comparative Example 3, the separate impregnation of the support with cerium and palladium resulted in lower hydrogenation efficiency. This demonstrates that the co-impregnation process of cerium and palladium can alter the electronic structure of the active components, optimize their geometry, and improve palladium dispersion, thus facilitating the full exposure of active sites and improving hydrogenation efficiency.

[0038] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention and not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing an anthraquinone hydrogenation catalyst, characterized in that, Includes the following steps: (1) A modified alumina carrier was obtained by impregnating the alumina carrier with a mixed solution of zirconium salt and zinc salt, followed by drying and calcination. (2) An anthraquinone hydrogenation catalyst is obtained by impregnating a modified alumina support with a mixed solution of cerium salt and palladium salt, followed by drying, calcination, and hydrogen reduction; wherein, based on the mass of the alumina support, the anthraquinone hydrogenation catalyst contains 2-4 wt% Zr, 1-2 wt% Zn, 0.08-0.15 wt% Ce, and 0.1-1 wt% Pd. In step (2), the drying temperature is 110-130℃; the calcination temperature is 550-600℃; and the calcination time is 2-4h.

2. The method for preparing anthraquinone hydrogenation catalyst as described in claim 1, characterized in that, The zirconium salt mentioned in step (1) is any one of zirconium nitrate, zirconium chloride, and zirconium sulfate; the zinc salt is any one of zinc chloride, zinc nitrate, zinc sulfate, and zinc acetate.

3. The method for preparing anthraquinone hydrogenation catalyst as described in claim 1, characterized in that, The alumina support mentioned in step (1) is γ-alumina with a specific surface area of ​​150-250 m². 2 / g, with a pore size of 6-12nm.

4. The method for preparing anthraquinone hydrogenation catalyst as described in claim 1, characterized in that, In step (1), the drying temperature is 100-130℃; the calcination temperature is 540-620℃; and the calcination time is 2-4h.

5. The method for preparing an anthraquinone hydrogenation catalyst as described in claim 1, characterized in that, The cerium salt mentioned in step (2) is either cerium nitrate or cerium chloride; the palladium salt is either palladium chloride or palladium acetate.

6. The method for preparing an anthraquinone hydrogenation catalyst as described in claim 1, characterized in that, The hydrogen reduction temperature in step (2) is 250-350℃.

7. The method for preparing an anthraquinone hydrogenation catalyst according to claim 1, characterized in that, The impregnation described in steps (1) and (2) is equal volume impregnation.

8. An anthraquinone hydrogenation catalyst, characterized in that, It is prepared by the method for preparing an anthraquinone hydrogenation catalyst according to any one of claims 1-7.

Citation Information

Patent Citations

  • Preparation method and application of supported Pd-based catalyst

    CN117816153A

  • Preparation method of hydrogenation catalyst for preparing H2O2

    CN105688901A

  • Single-atom palladium catalyst and preparation method and application thereof

    CN109939678A